If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 = 2y + 15 Reorder the terms: 49 = 15 + 2y Solving 49 = 15 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 49 + -2y = 15 + 2y + -2y Combine like terms: 2y + -2y = 0 49 + -2y = 15 + 0 49 + -2y = 15 Add '-49' to each side of the equation. 49 + -49 + -2y = 15 + -49 Combine like terms: 49 + -49 = 0 0 + -2y = 15 + -49 -2y = 15 + -49 Combine like terms: 15 + -49 = -34 -2y = -34 Divide each side by '-2'. y = 17 Simplifying y = 17
| 6-(4n-9)=4-5n | | =4(a+2) | | 5w-14=86 | | 0.05(n+1)+0.25=1.1 | | x=log(0.298) | | 210=6B+B | | -2/3p-4=-5/9p-15 | | =5(6c+4) | | =5(5c+4) | | 4-2g--10=-6g+2 | | y=5/6x-10 | | 2+3(6-2)= | | 2(3x+4)=1/3(x-1/2) | | x^2(x-5)+11(x-5)= | | 6(m+6)-5(6m-1)=-25(m-1)-10 | | x(x+16)-2(x+16)= | | 3x+5=-2-1 | | 6d=15+b | | (0.2)5x+1.75=0.75+0.25 | | 3x^4-21x^3+39x^2= | | (0.2)5x+1.75=0.75*0.25 | | 20=7n-3n | | 3m^2-5=94 | | 7-4c=11 | | 6(2x+6)=-3x+6 | | 2x^2+-5=0 | | 4x^2=20x-96 | | e-5x=7.4 | | (1-x)(2x+6)=0 | | (0.2)5x+1.75=0.75x+0.25 | | 4(2a-1)/9.6=10 | | 6x+1/2+1=x-3/3 |